How Facebook comments reflect certain characteristics of Chinese transnationalism identity: a preliminary research of netizens' comments on Sin Chew Daily Facebook page toward covid-19 Wuhan coronavirus outbreak - Lee, Yu Qian (2020)
This study is aimed to explore and analyse the reactions of the netizens on one of the popular social media, Facebook in Malaysian Chinese community toward the outbreak of COVID-19. It focuses on the media contents that solely posted by Sin Chew Daily on its Facebook page as well as the comments wrote by the Facebook users below. Through collecting and breaking down the comments of the Facebook users, this study further means to recognize how comments may mirror certain attributes of Chinese ethnonationalism and Chinese transnationalism identity, as well as to which topics in Facebook posts commentators relate on the most due to COVID-19 outbreak or so-called Wuhan Coronavirus. With the end goal of the study, four unique sorts of news articles identified with COVID-19 and the relating comments are analysed. All of the news articles that the paper will analyse are chosen from a trustworthy media source, Sin Chew Daily. Sin Chew Daily is among the major Chinese newspaper publications which having the most noteworthy readership and circulation in Malaysia. In order to provide deeper insights to fully understand the scope of study, theoretical frameworks for instance Jürgen Habermas’s Public Sphere Model and Stuart Hall’s Representation Theory were used.